Aerobic methanotrophy and co-occurrence networks of a tropical rainforest and oil palm plantations in Malaysia - Ho, Adrian; Tan, Ali Kee Zuan; Mendes, Lucas W.; Hyo, Jung Lee; Zulkeflee, Zufarzaana; van Dijk, Hester; Pil, Joo Kim; Horn, Marcus A. (Springer, 2021)
Oil palm (OP) plantations are gradually replacing tropical rainforest in Malaysia, one of the largest palm oil producers globally. Conversion of lands to OP plantations has been associated with compositional shifts of the microbial community, with consequences on the greenhouse gas (GHG) emissions. While the impact of the change in land use has recently been investigated for microorganisms involved in N2O emission, the response of the aerobic methanotrophs to OP agriculture remains to be determined. Here, we monitored the bacterial community composition, focusing on the aerobic methanotrophs, in OP agricultural soils since 2012, 2006, and 1993, as well as in a tropical rainforest, in 2019 and 2020. High-affinity methane uptake was confirmed, showing significantly lower rates in the OP plantations than in the tropical rainforest, but values increased with continuous OP agriculture. The bacterial, including the methanotrophic community composition, was modified with ongoing OP agriculture. The methanotrophic community composition was predominantly composed of unclassified methanotrophs, with the canonical (Methylocystis) and putative methanotrophs thought to catalyze high-affinity methane oxidation present at higher relative abundance in the oldest OP plantation. Results suggest that the methanotrophic community was relatively more stable within each site, exhibiting less temporal variations than the total bacterial community. Uncharacteristically, a 16S rRNA gene-based co-occurrence network analysis revealed a more complex and connected community in the OP agricultural soil, which may influence the resilience of the bacterial community to disturbances. Overall, we provide a first insight into the ecology and role of the aerobic methanotrophs as a methane sink in OP agricultural soils.